DISEÑO DEL MANUAL DE POLÍTICAS Y PROCEDIMIENTOS CONTABLES PARA LA COOPERATIVA DE AHORRO Y CRÉDITO “CRISTO REY” DE LA CIUDAD DE LOJA - Granda Granda, Jessica Paola (2019)
The thesis called "DESIGN OF THE MANUAL OF ACCOUNTING POLICIES AND PROCEDURES FOR THE SAVINGS AND CREDIT COOPERATIVE" CRISTO REY "OF THE CITY OF LOJA" was developed with the purpose of designing policies and procedures in the accounting area in order to bring an order logical and sequential of the activities that are executed in the cooperative. Through the use of methods and techniques to detect possible shortcomings in the management of accounting activities, and in this way staff and managers know the true situation of the entity. To achieve the aforementioned, it was necessary to comply with the specific objectives plated in the thesis work. It began to create accounting policies for each of the activities that are executed in the accounting office based on what is established in the unique catalog of accounts issued by the Superintendence of Popular and Solidarity Economy, which allowed to know the registry, norms and rules that must be followed for the proper functioning of the activities of the cooperative. Procedures were then defined according to each accounting policy in order to control the sequential order of the different activities performed by the accounting department, which help the executives of the entity to perform 5 their functions with truth and accuracy at the time of presenting the accounting and financial information. Finally, the manual of accounting policies and procedures was drawn up in which it contains the results with their respective flow diagrams; This document will allow the manager and managers of the position to make correct decisions that contribute to the continuous development of the cooperative. It is concluded that the manual of accounting policies and procedures is a tool that allows the executives of the entity to have a sequential order to record the accounting activities, since prior to the same a traditional record of the entity was kept, contributing of this way to make the entity more efficient in each of the operations carried out.